Orbit of influence: spy finance and the black budget. - Dreyfuss, Robert (American Prospect)
Although there is a legitimate place for secret intelligence operations in the modern state, political circumstances might suggest that the “intelligence-industrial complex,” like other government-dependent industries, is due for serious downsizing. A strong argument can be made that the cash outlays for the intelligence community's satellite reconnaissance systems and other aspects of its space program could be radically reduced. However, expenditures on the program are sustained by a voracious military appetite for ever greater quantities of intelligence data and by the power of lobbyists for and campaign money from the private industry that engineers, manufactures, and maintains the intelligence-industrial complex. Moreover, the CIA and the Pentagon today, perhaps more than at any other time in their history, are guided by leaders who are devoted to high-technology intelligence systems and who come directly out of industry.